THE APPLICATION OF NEW HABITS IN PREGNANT WOMEN AS AN EFFORT TO PREVENT THE SPREAD OF COVID-19 - Hairani; I Gusti Agung Ayu Hari Triandini; Nurrun Hasanah (JURNAL SANGKAREANG MATARAM, 2022)
Adaptation to New Habits in New Normal (ANH) is one form of effort in preventing the spread of COVID-19. The spread of the corona virus (COVID-19) is still categorized as a global public health emergency. This study reveals the level of compliance and knowledge in the application of ANH in the Karang Pule specially in Pande Besi. From a preliminary study conducted, there were 7 per 10 pregnant women who did not apply the adaptation of new habits during the ANC. The method used in this study was descriptive with a cross sectional perspective and questionnaires review. 30 respondents as sample conducted by distributing questionnaires. From the results of this study, it was found that the knowledge of pregnant women about COVID-19 in implementing adaptation of new habits was generally quite sufficient, as many as 14 respondents (46.7%) and the level of application of new habits of adaptation to pregnant women in the Pande Besi is generally quite sufficient, with 26 respondents (86.7%).